Delano's design overlay for historic preservation: an analysis of the overlay - Barnes, Matthew Wayne (Kansas State University, 2021)
Historic Districts, whether they are designated by the Federal, State, or local government, can be great economic tools to help foster financial investment in an area. However, the strict regulations that come with a designation may make developers wary of investing in the community. Similarly, in some instances, there can be a high level of population turnover if the residents living in the area before the creation of the district cannot afford to preserve their property to the expected standards. Design overlays, an alternative, can be used to preserve a neighborhood’s cohesiveness without the sometimes-strict regulations associated with historic districts. This report conducted a longitudinal case study analysis on the Delano Neighborhood in Wichita, Kansas, to research the impact of the design overlay placed on most of the district. Delano has seen a revitalization in the last 20 years with the addition of new apartments, the Advanced Learning Library, Riverfront Stadium, and other construction throughout the district. This study examined the demographic change for residents of Delano and property value change after the overlay was placed. Additional information was collected by speaking with a representative from the city of Wichita. The research then compared Delano to other regional overlays to understand where Delano was in the process of goal completion. Analysis of the data collected shows an initial increase in property values higher than that of the rest of the urban core in Wichita while maintaining a lower-income population. Despite the rise in property value, there was a high turnover in homeownership in the area, leading to the question of who reaped the benefits of the appraised property value increase. This longitudinal case study aimed to examine overlay districts as an alternative to regulated historic districts.
Keywords: Planning; Historic preservation; Design overlay; Zoning overlay; Delano; Wichita